Social Work, Risk, Power - Roger Smith
Contemporary ideas and strategies of both \'risk\' and \'power\' are significant and dynamic influences in social theory and social action, and they can therefore be expected to have a substantial impact on the ways in which social work is constituted, practiced and evaluated. In this article, I shall articulate distinct conceptualisations and debates about each of these, before considering their inter-relationships and the implications of these for our thinking about what social work is, and what it should be. Firstly, I will consider social work\'s contested and problematic place within the broader welfare domain. It is recognised as being a form of activity which inhabits an ambiguous and uncertain position at the interface between the individual and the social, and between the marginalised and the mainstream. Building on this, \'power\' will be shown to infuse social work ideas and practices in a number of distinct dimensions, linking and bridging \'personal\', \'positional\' and \'relational\' domains. This discussion will be juxtaposed with a discussion of \'risk\' and the part it has come to play in shaping and infusing social work practices, especially but not exclusively with children. The deconstruction of contemporary understandings and uses of risk as a central and \'authoritative\' feature of assessment and decision-making will inform the argument that it can be viewed as a vehicle for the maintenance and legitimation of power relations which disenfranchise and oppress those who are most vulnerable. In conclusion, I will summarise the ways in which conventional understandings and inter-related material realities of power and risk are often hierarchical, uni-directional and oppressive; and on this basis, how they can be laid open to challenge. The reconceptualisation and remaking of power relations will be shown to have direct consequences for the ways in which risk is defined and addressed as a social work \'problem\'.Social Work, Risk, Power, Social Justice, Authority, Legitimacy Left_arrows